2016
DOI: 10.1152/ajpregu.00131.2015
|View full text |Cite
|
Sign up to set email alerts
|

Aging-related impairment of urine-concentrating mechanisms correlates with dysregulation of adrenocortical angiotensin type 1 receptors in male Fischer rats

Abstract: To investigate age-associated impairments in fluid homeostasis, 4-mo (young) and 32-mo (old) Fischer 344/BN male rats were studied before and after a dietary sodium load. Transferring young rats from a low-sodium (LS) to a high-sodium (HS) diet increased water intake and urine volume by 1.9- and 3.0-fold, respectively, while urine osmolality and plasma aldosterone decreased by 33 and 98%. Concomitantly, adrenocortical angiotensin type 1 receptor (AT1R) density decreased by 35%, and AT1bR mRNA decreased by 39%;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Intervention scenarios involving the elderly did not yield great benefits in averting cases of AMI and stroke over the 30-year period from 2020 to 2050, since individuals in this high-risk stratum may have had long-term high salt intake and consequent organ damage. Regardless, this group should be prioritised as a key target group for salt-reduction interventions through careful management of their daily salt intake, which can effectively reduce their risk of mortality as well as improve their quality of life [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention scenarios involving the elderly did not yield great benefits in averting cases of AMI and stroke over the 30-year period from 2020 to 2050, since individuals in this high-risk stratum may have had long-term high salt intake and consequent organ damage. Regardless, this group should be prioritised as a key target group for salt-reduction interventions through careful management of their daily salt intake, which can effectively reduce their risk of mortality as well as improve their quality of life [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…(16) Research has shown that with advancement in age of humans and animals, they are less able to regulate sodium and water retention, urine concentration and thirst compared to their younger counterparts. (28) With increase in duration of smoking, there could be increase in sedentary behaviors and also increased physiological effects of nicotine (29) which could lead to an increase in body mass index. The lower values of serum myogenin seen in this study could be due to the presence of muscle stress caused by increase in age, frequency of smoking and duration of smoking.…”
Section: Discussionmentioning
confidence: 99%